Respostas

2014-05-18T15:00:37-03:00
A)7-106x = 20-54x
   -106x+54x = 20-7
            -52x = 13
                 x= 13 / -52
                 x= -0,25


b)5(x-7)-2(3x-1)=0
   5x-35-6x+2 =0
   5x-6x = -2+35
       -1x= 33
          x= 33
              ¨¨¨¨¨¨
               -1
           x=-33

c)3x-26-5x = 4+4(3x-20)
   3x-26-5x = 4+12x-80
   3x-5x-12x = 4-80+26
           -14x = -50
                x = -50
                     ¨¨¨¨¨¨
                      -14
                x = +3,57


Espero ter ajudado, abraço.